2000
DOI: 10.1097/00005053-200008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and Utilization of Medical Treatment Services among Male Vietnam Veterans

Abstract: This study investigated the effect of posttraumatic stress disorder (PTSD) on help-seeking for physical problems. Merging two large data sets resulted in a sample of 1773 male Vietnam veterans from white, black, Hispanic, Native Hawaiian, and Japanese American ethnic groups. Predictors of utilization included PTSD, other axis I disorders, and substance abuse. In analyses that adjusted only for age, PTSD was related to greater utilization of recent and lifetime VA medical services, and with recent inpatient car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 36 publications
8
68
1
Order By: Relevance
“…In other studies, PTSD has been hypothesized to be the "key mechanism" between trauma exposure and health outcomes, even after considering the high comorbity between PTSD and disorders such as depression and substance use, perhaps because of the toll of allostatic load (Schnurr and Green 2004;Schnurr and Spiro 1999;Wolfe et al 1994). Our study lends support to the literature documenting an independent effect of PTSD when comorbid conditions are examined (Boscarino and Chang 1999;Schnurr et al 2000). However, it should be noted that the comorbid conditions investigated in this study did not extend to other mental health concerns.…”
Section: Ptsd and Physical Healthsupporting
confidence: 81%
“…In other studies, PTSD has been hypothesized to be the "key mechanism" between trauma exposure and health outcomes, even after considering the high comorbity between PTSD and disorders such as depression and substance use, perhaps because of the toll of allostatic load (Schnurr and Green 2004;Schnurr and Spiro 1999;Wolfe et al 1994). Our study lends support to the literature documenting an independent effect of PTSD when comorbid conditions are examined (Boscarino and Chang 1999;Schnurr et al 2000). However, it should be noted that the comorbid conditions investigated in this study did not extend to other mental health concerns.…”
Section: Ptsd and Physical Healthsupporting
confidence: 81%
“…11,[15][16][17][18][19] In a study of 2,508 female veterans receiving care at an urban VA medical center between 1996 and 2000, Dobie and colleagues found that after adjusting for demographics, smoking, service access, and medical comorbidities, those who screened positive for PTSD had a significantly greater likelihood of having a medical or surgical hospitalization (OR 1.37, 95% CI 1.04-1.79). 11 They were also significantly more likely to be in the highest quartile of utilization for emergency room, primary care, and ancillary services.…”
Section: Discussionmentioning
confidence: 99%
“…6,[12][13][14] This increased burden of physical diseases may translate into greater non-mental health medical service utilization, as suggested by a study showing that PTSD was associated greater self-reported primary care visits in 2,863 OIF veterans 6 and by studies examining utilization in veterans of prior wars. 11,[15][16][17][18][19] Yet, mental disorders and their associated stigma and risk for social isolation and cognitive impairment may also act as barriers to medical treatment. 16,20 In addition, the unique features of the current wars, including the greater number of woman in combat roles and specific types of injuries (traumatic brain injury), could change utilization patterns and highlight the importance of studying this new cohort of veterans.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment needs of individuals with PTSD and chronic pain must also be addressed, especially given that they are likely to use more healthcare services [75][76][77]. Thus, VA healthcare providers should be informed about the various effects of PTSD treatment on veterans.…”
Section: Discussionmentioning
confidence: 99%